Long-term efficacy of everolimus as de novo immunosuppressant on the cardiac allograft vasculopathy in heart transplant recipients. (September 2022) - Choi, Hyo-In; Kang, Do-Yoon; Kim, Min-Seok; Lee, Sang Eun; Ahn, Jung-Min; Lee, Jong-Young; Kim, Yong-Hak; Park, Duk-Woo; Jung, Sung-Ho; Kim, Jae-Joong
Abstract: Background and aims: Data on the long-term effects of everolimus (EVL) on the de novo immunosuppression of heart transplant (HT) recipients with progressive cardiac allograft vasculopathy (CAV) and vascular remodeling are lacking. Hence, in this study, we aimed to determine the long-term safety and efficacy of EVL as a de novo immunosuppressant therapy for CAV progression and the clinical outcomes after HT. Methods: We retrospectively reviewed the medical records of 144 HT recipients who survived for at least one year after HT. CAV progression was assessed via serial coronary intravascular ultrasonography (IVUS) in recipients who underwent at least two IVUS studies. Results: A significant attenuation in the percentage of the atheroma volume progression was observed in those who took EVL (1.2%) compared with those who took cyclosporin (CSA; 7.3%; p = 0.005 vs. EVL) or tacrolimus (TAC; 6.6%; p = 0.0052 vs. EVL) at 1 year after HT. This trend persisted for the next 3 and 5 years after HT. Moreover, the remodeling index was greater in the EVL (1.08) group than in the CSA (0.23) or TAC (−0.25) groups 1 year after HT. The results of the Kaplan–Meier analysis over a median follow-up period of 8 years revealed that there was no statistical difference in the primary endpoint between the three groups. Conclusions: De novo immunosuppression with EVL is associated with attenuated CAV progression for the first 5 years of follow-up via IVUS. Moreover, EVL has comparable long-term clinical outcomes to those of CSA- or TAC-based protocols. Graphical abstract: Image 1 Highlights: Data on cardiac allograft vasculopathy progression in everolimus-immunosuppressed heart recipients are scarce. Everolimus is associated with reduced plaque progression and positive vascular remodeling. De novo everolimus is an effective immunosuppressant therapy.